Green products purchasing behaviour in Malaysia : an exploratory study - Zein, Zariyah Ibrahim M. (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2014)
Green marketing has become an area of great importance, especially in the context of Malaysia. As Malaysia seeks to establish a balance between development and conservation, it is of utmost importance for research on consumer's behaviour to done. Hence, this research attempts to explore the Malaysian consumers purchase behaviour towards green products. With the use of the plethora of literature that currently exists, a theoretical framework was constructed in order to meet the objectives of the study. For this empirical study primary data was collected with the use of a self administered questionnaire. With the use of 231 questionnaires from Malaysian respondents, analysis was conducted using both stage Statistical Package for Social Sciences (SPSS) And Analysis of Moment Structure AMOS. At the beginning SPSS was used to conduct the Descriptive analysis and later on the exploratory factor analysis (EFA) was done. At the second stage Confimatory factor analysis and structural equation modelling was done using AMOS. The findings of the study have inducted that a significant positive relationship exists between Malaysian customers' green knowledge and their purchase intention and behaviour. It was also noted that when it comes to consumers' green attitude towards their purchase intention as well as their behaviour a significant relationship is evident. It was made clear that consumer's willingness to pay had a significant negative effect on their purchase intention. When it comes to green advertisement it was found that consumers purchase intention didn't have a significant positive relationship with green advertisement. Additionally consumers green purchase intention and their behaviour was found to have a significant positive relationship.